92.4k views
3 votes
Could someone please explain this to me step-by-step?

Could someone please explain this to me step-by-step?-example-1
User Isklenar
by
5.2k points

1 Answer

6 votes

Step 1


( \frac{6d}{d {}^(4) } ) {}^( - 2) \\

Take the reciprocal of the inside to get rid of the negative exponent.

note: reciprocal=flip it over


( \frac{6d}{d {}^(4) } ) {}^( - 2) = ( \frac{d {}^(4) }{6d} ) {}^(2) \\

Step 2

Before we continue we can notice that the inside is reducible since we have d's in the numerator and the denominator.

note: d=d^1

Using the Law of Exponents:


\frac{a {}^(m) }{a {}^(n) } = a {}^(m - n) \\


( \frac{d {}^(4) }{6d} ) {}^(2) =( (1)/(6) * \frac{d {}^(4) }{d}) = ( \frac{d {}^(4 - 1) }{6} ) {}^(2) = ( \frac{d {}^(3) }{6} ) {}^(2) \\

Step 3


note \: that \\ ( ( \omega)/( \eta) ) {}^(x) = \frac{ \omega {}^(x) }{ \eta {}^(x) }


( \frac{d {}^(3) }{6} ) {}^(2) = \frac{(d {}^(3)) {}^(2) }{6 {}^(2) } = \frac{d {}^(3 * 2) }{36} = \frac{d {}^(6) }{36} \\

User Aqueel
by
4.5k points